Management system for the restoration of the machine-building complex of Ukraine - N.A. Yefimenko (Економіка, управління та адміністрування)
The article proposes an algorithm for restoring the machine-building complex of Ukraine in wartime. Considerable attention was paid to the restoration of capital, taking into account the specifics of machine-building enterprises to improve the quality parameters of production.